Padrões e processos ecológicos do componente arbóreo em uma área de floresta estacional semidecidual (Araguari, MG) - Vale, Vagner Santiago do (2008)
This thesis deals with the study of the tree component in a seasonal semideciduous forest (FES) with a good state of conservation. Initially, it was prepare a general introduction, showing the importance of the detailing study of forests well preserved, as comparative basis with disturbed forests. After this context, the thesis has been divided into two chapters. The first chapter tries to characterize the tree component of a hectare of FES, through the studies of floristic composition and horizontal and vertical structure, and the characterization of the soil. The species were classified accord the dominant stratum and in sucessional group. In this chapter were calculate the floristic similarities with other FES southeastern Brazil, based on the richness and abundance. In the second chapter was searched the formation of functional groups based on ecological attributes of the species. Therefore, it was used a similarity s dendrogram based on the presence/absence of attributes. The results showed that even in preserved forests have high spatial heterogeneity caused by natural gaps. The division of groups successional point to the concentration of late secondary species and low presence of pioneers in the strata. The similarity s analysis based on richness allowed the formation of four groups, and the similarity based on the abundance allowed closer areas with similar degree of conservation, even approaching the FES studied with other FESs in well conserved stage. These results demonstrate the high degree of maturity of the FES studied. In the delimitation of functional groups, four major groups were determined by their attributes: G1 - ornitocoric and light-demanding group; G2 - mastocoric and canopy light-demanding group; G3 - canopy, abiotic dispersion group and G4 - ornitocoric, shade-tolerant and the only group predominant in the understory. The G4 was the more abundant group. It was concluded that the tree community, although present natural gaps, is in a mature stage; the proximity between fragments of FES is a determinant factor in the floristic composition; fragments in similar conservation state have higher floristic similarity; the community tree has, at least, four big functional groups, which play different function in the ecosystem. The results obtained here have great contribution to the understanding of the ecological patterns and processes involved in these ecosystems. But there is a need for further studies that can for detail the communities tree structure and involves the formation of functional groups for better understanding of high diversity forests.